Growth and yield of turmeric (Curcuma longa L.) intercropped in poplar (Populus deltoides Bartram ex Marshall) plantation at Punjab - N Gandhi, Jaspreet Kaur, B S Gill, A Singh, Devinder Singh (Journal of Spices and Aromatic Crops, 2009)
The effect of planting dates and methods of planting of turmeric (Curcuma longa) intercroppedin poplar (clone Udai) (Poplulus deltoides) plantation was studied at Ludhiana (Punjab,India). The treatments consisted of three planting dates namely, 20th March, 20th April and20th May and two methods of planting, namely, ridge and flat method (60 cm x 10 cm) inpoplar plantation. The study revealed that in first year of plantation (2004-05), a fresh rhizomeyield of 9.96 t ha-1 was obtained in 20th April planting which was significantly more thanthat of 20th May planting (9.45 t ha-1). During 2005-06, a fresh rhizome yield of 8.15, 11.61and 13.95 t ha-1 was produced in 20th March, 20th April and 20th May planting dates, respectively.During 2006-07, the yields were lower and the differences in fresh rhizome yield due to 20thMay (6.33 t ha-1) and 20th April (6.43 t ha-1) planting were not significant but both theplanting dates were significantly better than 20th March (5.6 t ha-1) planting. The ridge methodof planting produced 8.0%, 11.0% and 9.8% more yield which was significantly higher thanflat method of planting during 2004-05, 2005-06 and 2006-07, respectively.